2011
DOI: 10.3109/03630269.2011.571527
|View full text |Cite
|
Sign up to set email alerts
|

The Carrier Frequency of α-Globin Gene Triplication in an Iranian Population with Normal or Borderline Hematological Parameters

Abstract: The -α(3.7) rightward deletion is the most frequent α-globin mutation worldwide, while frequencies of the ααα(anti 3.7) triplication are only sporadically known. Carriers of the ααα(anti 3.7) triplication show no clinical symptoms or significant hematological changes, but co-inheritance with β-thalassemia (β-thal) has been reported to worsen the clinical and hematological features of the patient as well as the trait. We have screened the α-globin gene rearrangements of 280 individuals with normal hematological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…These results show that -a 3.7 gene deletion is prevalent worldwide including our country and indicate that our results are in agreement with literature. The -a 3.7 deletion is the most frequent a-globin mutation, while frequencies of the aaa anti-3.7 triplication are only sporadically known [23]. The aaa anti-3.7 triplication was found lower than -a 3.7 deletion in our study, similar to other studies worldwide.…”
Section: Discussionsupporting
confidence: 89%
“…These results show that -a 3.7 gene deletion is prevalent worldwide including our country and indicate that our results are in agreement with literature. The -a 3.7 deletion is the most frequent a-globin mutation, while frequencies of the aaa anti-3.7 triplication are only sporadically known [23]. The aaa anti-3.7 triplication was found lower than -a 3.7 deletion in our study, similar to other studies worldwide.…”
Section: Discussionsupporting
confidence: 89%
“…The molecular analysis of the alfa globin genes highlighted an anti 3.7 Kb gene triplication heterozygous mutation (see Figure 2). Carriers of this mutation show no clinical symptoms or hematological changes, although a considerable amount of literature has reported that the existence of this mutation with mutations in β globin genes worsens the clinical characteristics of the patient, as it has been found in this case [9] . Figure 1.…”
Section: Resultsmentioning
confidence: 47%
“…4 Nevertheless, in another study on Tehran population, the frequency of this mutation was reported to be close to Mazandaran (2.14%). 20 Comparing all the available studies in different provinces of Iran, one may conclude that the total carrier frequency of alpha globin gene mutations is similar in different regions of Iran; however, the spectra of mutations Comparing to Mazandaran province, frequency of alpha thalassemia carriers is higher in UAE, but it has to be noted this high frequency rate is mostly due to high allelic frequency of -α 3.7 deletion in that population (0.2847 in UAE versus 0.0485 in Mazandaran), but if we compare the next common mutations in the two populations, we realize that other mutations do not have very high frequencies in UAE and for instance, -α 4.2 deletion which is the second most common mutation in both societies, has a higher allelic frequency rate in Mazandaran (0.0072 versus 0.0206). The results of similar studies from Southeast Asia, Brazil, and Georgia have shown that carriers with -α 3.7 deletion are more common than other alpha thalassemia gene mutations, and this mutation has to be considered the most common alpha globin gene mutation worldwide.…”
Section: Discussionmentioning
confidence: 97%